Determinants of Traders’ Income at the Revitalized Vs Non-Revitalized Traditional Wet Market - Anindya Rahayu Pratami; Rakhmat Priyono; Arintoko Arintoko (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2019)
The modern market has made the wet market have to change its appearance to be able to provide competitiveness with the modern market. Therefore, in this study comparing wet markets that have been revitalized (Manis Market) and not revitalized (Pon Market) in Purwokerto. In this research, to analyze the influence of several factors such as capital, working hours and length of business on the income of traders and to analyze differences in the average income of traders in Manis Market and Pon Market. The data used in this research are primary data taken from 84 respondents from Manis Market and 55 respondents from Pon Market. The results of multiple linear regression analysis show that capital has a significant influence on the income of traders while other factors such as working hours and length of business do not significantly influence the income of traders in the Manis Market. Then the capital and duration of the business have a significant influence on the income of traders while other factors such as working hours do not significantly influence the income of traders in Pon Market. Result of Independent Sample t-test also shows that there are significant differences in the average income of traders between Manis Market and Pon Market. Thus, revitalization is still a factor that can enhance the competitiveness of traditional markets.Keywords: income, capital, working hours, length of business, and revitalization